2019
DOI: 10.1192/bjp.2019.226
|View full text |Cite
|
Sign up to set email alerts
|

Authors’ reply

Abstract: Edited by Kiriakos Xenitidis and Colin Campbell Contents ▪ Prevalence: are two-fifths of young people really 'abnormal'? ▪ Authors' reply Prevalence: are two-fifths of young people really 'abnormal'? We read with interest Deighton and colleagues' paper about mental health problems among 11-to 14-year-olds. 1 They stress the importance of understanding prevalence and report 'findings that indicate the scale of mental health problems in England is much higher than previous estimates'. The previous estimates refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Though the self-report SDQ is widely used, including to study age differences (Deighton et al, 2019;Hafekost et al, 2016;Johnston & Gowers, 2005), evidence of its age SDQ AGE APPROPRIATENESS 18 appropriateness has been limited. Building on existing evidence (He et al, 2013;Patalay et al, 2018) we addressed this gap by considering the measure's item-level readability, item quality, factor structure, and age measurement invariance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though the self-report SDQ is widely used, including to study age differences (Deighton et al, 2019;Hafekost et al, 2016;Johnston & Gowers, 2005), evidence of its age SDQ AGE APPROPRIATENESS 18 appropriateness has been limited. Building on existing evidence (He et al, 2013;Patalay et al, 2018) we addressed this gap by considering the measure's item-level readability, item quality, factor structure, and age measurement invariance.…”
Section: Discussionmentioning
confidence: 99%
“…Where measures lack proposed dimensionality, as is the case with the self-report SDQ (Goodman et al, 2010;Goodman, 2001;Percy et al, 2008), and invariance testing is warranted, given recent claims about age (Deighton et al, 2019;Dray et al, 2016;NHS Digital, 2018), exploratory structural equation modelling (ESEM) techniques can be used (Marsh, Nagengast, & Morin, 2013a). As others have pointed out, though ESEM structures should not be used to conceal problems with a measure, they can provide a more realistic framework for measurement invariance analysis where CFA models do not fit sufficiently well (Tóth-Király, Bõthe, Rigó, & Orosz, 2017).…”
Section: Item Quality Criteria Consistent With Readability Indices Psychometric Guidancementioning
confidence: 99%
See 2 more Smart Citations
“…One in five adolescents experience symptoms of poor mental health, such as depression or anxiety (Deighton et al, 2018). A recent meta-analysis, showed that 41.5% of individuals experience their first symptoms by the age of 14 years old, irrespective of the mental illness diagnosis (Solmi et al, 2021).…”
mentioning
confidence: 99%